An Empirical Analysis of Competition in Print Advertising among Paid and Free Newspapers. Issue 310 (25th June 2019) - Brooke, Geoffrey; Cheung, Lydia
Abstract : This paper examines competition in the print newspaper advertising market in New Zealand, which involves paid daily and free weekly titles. This is the first study to explore how different ownership structures across two newspaper segments affect the competitive forces in local geographic markets. We do so by constructing an original dataset of advertising rates. Our analysis has particular relevance in light of the Commerce Commission's recent rejection of the proposed NZME–Fairfax merger, and Fairfax's subsequent closure of 15 newspaper titles. We find strong evidence for competition between overlapping free weekly suburban titles. It is associated with an 11 per cent decrease in the tabloid full‐page display advertising rate. We also find evidence of joint profit maximisation between co‐owned free weeklies and paid dailies. Our results support the Commission's decision and crucially imply that small and large display advertisements in free weekly titles constitute two separate markets with different clients. The large display ad market also includes advertising in paid daily titles. This market is competitive and would probably have suffered had the merger been permitted.